NEGOTIATING IDENTITY AND POWER THROUGH ANGER: A SOCIO-PRAGMATIC STUDY OF JAVANESE MINORITY VOICES IN DIGITAL INTERACTION - Rahardi, R. Kunjana; Rahmat, Wahyudi (Journal of Pragmatics and Discourse Research, 2026)
This study investigates how anger functions as a communicative strategy for negotiating identity, power, and social hierarchy within the context of Javanese interaction, particularly among speakers who represent a cultural minority within Indonesia’s broader linguistic landscape. Moving beyond universalist interpretations of anger as purely an emotional outburst, this study conceptualizes anger as a culturally situated and socially meaningful act. Using a socio-pragmatic framework grounded in Goffman’s face theory and Brown and Levinson’s politeness model, the study qualitatively analyzes naturally occurring expressions of anger collected from Javanese digital discourse. The analysis reveals that anger is not merely an antisocial or impolite act but a pragmatic performance that affirms self-worth, challenges authority, and restores disrupted social balance. Five dominant identity functions of anger emerge: self-assertion, defense of dignity, moral correction, contestation of disrespect, and negotiation of masculinity. These functions highlight how anger, while face-threatening, becomes a resource for identity positioning and community solidarity within Javanese cultural logic. Furthermore, digital environments allow speakers to reframe traditional norms of emotional restraint, reflecting a generational shift in how minority identities express moral and social legitimacy. The study contributes to understanding the intersection between culture, emotion, and discourse by revealing how anger articulates both vulnerability and empowerment within culturally embedded communicative systems.